Integrity zone as a self-regulation strategy against abused discretionary power and corruption among Indonesia’s government offices - Hadyan Iman Prasetya (Integritas: Jurnal Antikorupsi, 2025)
Indonesia has been implementing the integrity zone program for ten years. The program aims to reform and establish a corruption-free and clean bureaucracy. However, the recent phenomenon shows that the program still needs refinement. This article offers a novel and alternative theoretical concept in explaining the program: self-regulation. Using normative legal research coupled with doctrinal and conceptual approaches, this Article argues that self-regulation offers a democratic strength to the integrity zone program. Perceiving the integrity zone program as a self-regulation strategy means that the government limits its discretionary power and prevents the abusive exercise of such power, which in turn could contribute to corruption eradication measures. Besides offering a novel explanation, the self-regulation concept could strengthen the democratic aspects of the integrity zone program. An effective self-regulatory strategy entails a deliberative forum for the regulated parties’ members and could invite intervention by external institutions representing the checks and balances principle. Therefore, perceiving the integrity zone program as a self-regulatory strategy could empower the government agencies’ employees to participate and be deliberately involved in the process of establishing the zone of integrity within their organizations. It could also activate the enforcement of such self-regulatory rules by the court and the legislature.